2020
DOI: 10.1017/npt.2020.26
|View full text |Cite
|
Sign up to set email alerts
|

Studying autocratization in Turkey: political institutions, populism, and neoliberalism

Abstract: In this review article I classify the literature on the Turkish political regime during Justice and Development Party rule as two waves of studies, and a potential third wave. The first wave was prevalent at least until the Gezi uprisings in 2013. I argue that, in this wave, the main debate was between two rival and largely culturalist perspectives with conceptual toolkits that tended to interpret regime change through the lens of social transformations. I also maintain that scholarly works written from the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Adalet ve Kalkınma Partisi (AKP), iktidara geldiği ilk dönemde yukarıda tartışılan demokratikleşme yolunda attığı adımlar sonrasında popülist ve otoriter bir dönüşüm yaşamıştır (Başer & Öztürk, 2017;Öktem & Akkoyunlu, 2016;Somer, 2016) ve bu, siyasi kültürün dönüşümüne etki etmiştir. AKP hükümetinin halkın demokratik iradesi üzerine inşa edilen çoğunlukçu bir anlayışa dayanan popülizmi (Özbudun, 2014;Sözen, 2020;Aytaç ve Öniş, 2014;Dinçşahin, 2012), zamanla "rekabetçi otoriterlik" (Castaldo, 2018;Esen ve Gümüşçü, 2016) veya hibrid rejim (Öniş, 2016) olarak nitelendirilmiştir. AKP'nin "otoriter neoliberal" politikaları ile yürütmenin merkezileştirilmesi ve muhalefetin kriminalize edilmesi gibi stratejilerle yasal ve idari rollerini güçlendirdiği ve halkın katılımını engellediği tartışılmıştır (Borsuk vd., 2021).…”
Section: Günümüzde Türkiye'de Vatandaşlık Dinamikleriunclassified
“…Adalet ve Kalkınma Partisi (AKP), iktidara geldiği ilk dönemde yukarıda tartışılan demokratikleşme yolunda attığı adımlar sonrasında popülist ve otoriter bir dönüşüm yaşamıştır (Başer & Öztürk, 2017;Öktem & Akkoyunlu, 2016;Somer, 2016) ve bu, siyasi kültürün dönüşümüne etki etmiştir. AKP hükümetinin halkın demokratik iradesi üzerine inşa edilen çoğunlukçu bir anlayışa dayanan popülizmi (Özbudun, 2014;Sözen, 2020;Aytaç ve Öniş, 2014;Dinçşahin, 2012), zamanla "rekabetçi otoriterlik" (Castaldo, 2018;Esen ve Gümüşçü, 2016) veya hibrid rejim (Öniş, 2016) olarak nitelendirilmiştir. AKP'nin "otoriter neoliberal" politikaları ile yürütmenin merkezileştirilmesi ve muhalefetin kriminalize edilmesi gibi stratejilerle yasal ve idari rollerini güçlendirdiği ve halkın katılımını engellediği tartışılmıştır (Borsuk vd., 2021).…”
Section: Günümüzde Türkiye'de Vatandaşlık Dinamikleriunclassified
“…The mass protests were unexpected for the government, resulting in repressive measures against the democratic right to protest (Atak and della Porta 2016) and leaving eleven casualties and 189 arrests behind (Welle 2016;International Federation for Human Rights 2014). Studies have suggested that the AKP started to take a more authoritarian turn after the Gezi protests to deter similar incidents of mass opposition (Sözen 2020). Shortly after protests spread to the entire nation, Recep Tayyip Erdoğan, the then prime minister of the government, said 'we are barely keeping 50% of the population at home' (Hürriyet 2013), implying that the other half of the population that is supposedly supported the AKP government was not on the streets demonstrating yet was ready to show support for the government instead.…”
Section: Contentious Politics In An Authoritarian Turkey During 2013-...mentioning
confidence: 99%
“…For example, the result of the 2010 referendum further curtailed the independence of the judiciary (Kalaycıoğlu, 2012). Also, especially after the 2013 Gezi uprising, the government's suppression of personal rights and freedoms heightened (Sözen, 2020).…”
Section: Case Selection: Democratic Backsliding In Turkeymentioning
confidence: 99%